Customer requirements and the quality improvement of health care services = Rola klienta w doskonaleniu jakości usług medycznych - Ludwiczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
Customer oriented approach is at present the most important principle in quality management. It becomes particularly significant in the context of offering the society high standard health care services. The aim of the research presented in the paper is to diagnose the functioning of customer oriented approach in Polish hospitals, and in particular actions in respect of meeting customer requirements at the stage of developing and improving health care services.
Keywords: orientacja na klienta; usługi medyczne; system zarządzania jakością; customer orientation; health care services; quality management system